2015
DOI: 10.5455/njppp.2015.5.241120141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition and socioeconomic status on intellectual development in school children

Abstract: Background: The nutritional adequacy is one of the determinants of quality of human resources everywhere. Malnutrition is the root cause for the death of 6 million children each year in developing countries. Nutritional deficiency is correlated with an increased risk of impaired cognitive function in children. Aims and Objective: To assess the role of nutrition and socioeconomic status on the development of IQ in school children. Materials and Methods: A cross-sectional, observational study was carried out in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…A longitudinal study assessing 1,674 children by the Peabody Picture Vocabulary Test showed that only one‐third of children who were stunted in infancy at 1 year of age, recovered by the time they were 5 years old 16 . In another study, the IQ was calculated in 200 children using Kamat's psychological test and 29.3% of those malnourished were classified with below average IQ compared to the 11.5% of children with normal nutritional status 17 . Finally, two studies assessing the IQ by RPCM showed a higher prevalence of malnourished children with below average IQ compared to normal nutritional status (68.7% vs 15.9%) and (83.3% vs 44.3%), respectively 18,19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study assessing 1,674 children by the Peabody Picture Vocabulary Test showed that only one‐third of children who were stunted in infancy at 1 year of age, recovered by the time they were 5 years old 16 . In another study, the IQ was calculated in 200 children using Kamat's psychological test and 29.3% of those malnourished were classified with below average IQ compared to the 11.5% of children with normal nutritional status 17 . Finally, two studies assessing the IQ by RPCM showed a higher prevalence of malnourished children with below average IQ compared to normal nutritional status (68.7% vs 15.9%) and (83.3% vs 44.3%), respectively 18,19 …”
Section: Resultsmentioning
confidence: 99%
“…16 In another study, the IQ was calculated in 200 children using Kamat's psychological test and 29.3% of those malnourished were classified with below average IQ compared to the 11.5% of children with normal nutritional status. 17 Finally, two studies assessing the IQ by RPCM showed a higher prevalence of malnourished children with below average IQ compared to normal nutritional status (68.7% vs 15.9%) and (83.3% vs 44.3%), respectively. 18,19 The overall mean score of the studies was 6.5 (range: 5-8), indicating an overall good quality, according to the NOS (Table S2).…”
Section: Re Sultsmentioning
confidence: 96%
“…Furthermore, malnourished children suffer from deficient motivation, investigative skills and interest. In some districts of India, between 54.5% and 57.65% of children (1-6 years old) are malnourished (Garkal & Shete 2015). Overall, India has four times poor than wealthy residents.…”
Section: Socio-economic Trendsmentioning
confidence: 99%
“…In developing countries, 200 million children aged 5 or less are hindered from reaching their full cognitive development and school achievements [ 1 ] because of social health inequalities [ 2 , 3 , 4 ]. Their cognitive abilities are plagued by political, socio-economic, educational, and environmental issues that include poverty, malnutrition, violence exposure, and toxic element hazards among the most prominent casualties [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their cognitive abilities are plagued by political, socio-economic, educational, and environmental issues that include poverty, malnutrition, violence exposure, and toxic element hazards among the most prominent casualties [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Malnutrition is a major health issue as it increases childhood morbidity and mortality (6 million deaths per year in developing countries) and leads to permanent impairment of physical and mental growth [ 21 ], most particularly in low-income countries (LICs) [ 2 , 3 , 22 , 23 , 24 , 25 , 26 ]. Socio-economic status (as expressed by poverty status) is the other well-known predictor to impeding children’s cognitive development, as evidenced in LICs such as Chile, Iran, Nepal, India, and Malaysia [ 2 , 3 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%